Ethnoveterinary study of medicinal plants in Mehrabad village, Shahrbabak city, Kerman Province, Iran - Navid Hassan abadi; Elham Khoshbin; Zahra Mahdavi Meymand (Islamic Azad University, Shahrekord Branch, 2022)
Background & Aim: The Mehrabad village people in Shahrbabak and Province Kerman, Southeast Iran, have used medicinal plants and traditional remedies for ethnoveterinary practices, such as treating domestic animals during livestock breeding, since ancient times. Experimental: This study aimed to identify the plants used in their conventional ethnoveterinary methods and to propose suggestions for future conservation and sustainable use of this knowledge between 2019 and 2020. Data were collected from the local Buyi people through semi-structured interviews. Results: A total of 36 plant species, belonging to 25 families, used in ethnoveterinary practices by the Mehrabad people. During the survey, it was observed that the most prevalent families concerning the number of species were Apiaceae (13.51%), Followed by Papilionaceae (10.81%) followed by Chenopodiaceae, Lamiaceae, Liliaceae, Rosaceae, and Solanaceae (5.40% each), and the remaining families (2.70%) species. Sources and habits of medicinal plant types of growth that were herbs (60.97%), shrubs (24.39%), and trees (14.63%). Leaves (23.80%) were the most widely used plant parts for ethnoveterinary medicine, followed by Seeds (19.05), Aerial parts (19.05), and Fruits (16.66). Oral administration was the most common (70.45. %), followed by cutaneous (topical) administration (13.63%), chewing (9.09%), and smoking (6.81%). Older farmers had more excellent EVM knowledge than those who were younger. Recommended applications/industries: The information obtained in this study may help in the use and discovery of new drugs and further studies are needed to prevent the extinction of traditional veterinary knowledge (ethnoveterinary). Oral administration was the most common (42.76%), followed by cutaneous (topical) administration (36.18%).